2014
DOI: 10.3390/molecules191221442
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Depressant-Like Effect of Kaempferitrin Isolated from Justicia spicigera Schltdl (Acanthaceae) in Two Behavior Models in Mice: Evidence for the Involvement of the Serotonergic System

Abstract: Abstract:We evaluated the antidepressant-like effect of kaempferitrin (Km) isolated from the plant Justicia spicigera (Asteraceae), which is used in traditional medicine for relieving emotional disorders, such as "la tristeza" (sadness or dysthymia) and "el humor" (mood changes). The actions of Km were evaluated in a forced swimming test (FST) and a suspension tail test (TST) in mice. We explored the involvement of the serotonergic system and the hypothalamic-hypophysis-adrenal axis (HPA) in the antidepressant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 54 publications
0
25
0
1
Order By: Relevance
“…This broad review constitutes a significant contribution to our understanding of the mechanisms of action that allow plants to produce antidepressant and anxiolytic effects (see Figure 1 for a summary). However, most of the studies reviewed were conducted with mice, due to the low yields achieved when isolating the metabolites of plant extracts [95], which limit the amount of testing that can be done. Another concern is that some infusions or extracts used as household remedies lose their antidepressant or anxiolytic effects when fractioned [96].…”
Section: Final Comments and Conclusionmentioning
confidence: 99%
“…This broad review constitutes a significant contribution to our understanding of the mechanisms of action that allow plants to produce antidepressant and anxiolytic effects (see Figure 1 for a summary). However, most of the studies reviewed were conducted with mice, due to the low yields achieved when isolating the metabolites of plant extracts [95], which limit the amount of testing that can be done. Another concern is that some infusions or extracts used as household remedies lose their antidepressant or anxiolytic effects when fractioned [96].…”
Section: Final Comments and Conclusionmentioning
confidence: 99%
“…Kaempferitrin (Figure a) is a natural flavonoid glycoside that has been found in several edible and medicinal plants (Hamzah, Lajis, & Sargent, ). Kaempferitrin has been reported to possess broad bioactivities, such as antioxidative (Vellosa et al, ), anti‐inflammatory (De Melo et al, ), anticonvulsant (Gonzalez‐Trujano et al, ), antidepressant (Cassani, Dorantes‐Barron, Novales, Real, & Estrada‐Reyes, ), antidiabetic (Da Silva et al, ), and antitumor activities (Alonso‐Castro et al, ). It has been demonstrated that flavonoids have a protective effect against RA, which in part own to its anti‐inflammatory activity (Bala, Chetia, Dolai, Khandelwal, & Haldar, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several scientific investigations have explored the biological properties of B. forficata , demonstrating, in addition to the hypoglycemic activity already mentioned in the section, its potential effect as an antioxidant (Miceli et al, ; Salgueiro et al, ), an anticoagulant, an antifibrinogenolytic against snake venoms (Oliveira et al, ), and now for the first time as shown here in our study, as a diuretic agent. Moreover, as described in the following paragraphs, kaempferitrin, the major natural constituent isolated from B. forficata leaves, also demonstrated the diuretic and natriuretic properties when given to rats, adding to their biological effects already described in previous studies, which showed their beneficial effect in the prevention of bone loss in ovariectomized rats (Ma et al, ), the stimulation of glucose uptake in skeletal muscle (Cazarolli et al, ) and an antidepressant‐like effect (Cassani et al, ).…”
Section: Resultsmentioning
confidence: 79%